(untitled) (Research, Society and Development, 2020)
Seeking to resolve part of the obstacles that stand in the way of meaningful learning of concepts associated with Electricity when worked in Physics classes in High School, largely from “traditional” pedagogies that prioritize classes centered on the teacher and memorization at the expense of dynamism and practical understanding, we present this work for appreciation. Its main objective is to build a didactic sequence on the theme related to studies in the field of electricity, having as theoretical basis the Pestalozzian method of teaching, the conceptualization of meaningful learning by Ausubel and the use of generating themes as defined by Paulo Freire, as a guideline of a methodology that transfers to the student the role of learning itself, Problem Based Learning (PBL). The results obtained from the implementation of the didactic sequence in a class of 3rd grade of High School were analyzed meticulously, and point to the occurrence of meaningful learning, the target of teaching practice.